Effects of exercise mode and intensity on patient-reported outcomes in cancer survivors: a four-arm intervention trial - Pelzer, Fabian; Leisge, Kai; Schlüter, Kathrin; Schneider, Justine; Wiskemann, Joachim; Rosenberger, Friederike (Supportive care in cancer, 2023)
The aim of this study was to compare the effects of different exercise modes (aerobic, resistance) and intensity prescriptions (standard, polarized, undulating) on patient-reported outcomes (PROs) in cancer survivors.